(untitled) (Research, Society and Development, 2021)
The work of the speech therapist in the neonatal Intensive Care Unit is of fundamental importance in detecting changes in the sensory-motor-oral system, especially in relation to the coordination of the sucking, swallowing and breathing functions in newborns. Therefore, this study aims to analyze the main benefits related to speech therapy in the neonatal ICU. Regarding the methodology, the present work is an integrative literature review study. The inclusion criteria established to select published articles were as follows: published in electronic format in the period from 2015 to 2020; available in full and free of charge, translated into Portuguese, which contemplate the benefits of speech therapy in the neonatal ICU. The exclusion criteria adopted were: articles published in languages ​​other than Portuguese; articles published outside the established period, articles that did not fit the objectives of the work, those whose texts were not in full, in addition to letters, editorials and comments. An integrative review study was carried out on the articles published in the databases of the Latin American and Caribbean Literature in Health Sciences databases (LILACS), Scielo and the Online Medical Literature Search and Analysis System (MEDLINE) as they are free to access and scientific, in the period from 2013 to 2017. It was found through this research that speech therapy intervention in the early stimulation of sucking in newborns is quite effective, being directly related to hospital discharge, as well as in the overall development of the baby, moreover, through early stimulation by the speech-language pathologists in newborns is fundamental for feeding in the mother’s breast, based on pleasure and very functional, contributing to the reduction of the time period of hospitalization.